Relationship between seed survival and seed characteristics of nine Mediterranean legumes after ingestion by sheep - Cardoso J.A.; Zaitegui M.; Robles A.B. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
The present work examines the relationship between different seed characteristics (seed size: length and width, seed form, seed volume, seed mass and hardseededness) and seed survival of nine legumes adapted to Mediterranean environments after ingestion by sheep (Segureña breed). Species used in the present study include: Trigonella polyceratia L., Bituminaria bituminosa (L.) C.H. Stirt, Lathyrus filiformis (Lam.) J. Gay, Vicia peregrina L., V. ervilia (L.) Willd, two V. sativa L. (a commercial cultivar and a wild one) and two Medicago sativa L. (a commercial cultivar and a wild one). Our results show that apart from hardseededness (R2=0.83), none of the chosen seed attributes were able to explain the relationship between survival and seed characteristics. For legumes and other species with physical dormancy the proportion of hardseededness could be a useful approach to assess endozoochorous seed dispersal potential.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)